The practical approach to the evaluation of methods used to determine the disintegration time of orally disintegrating tablets (ODTs) - Brniak, Witold (Saudi Pharm J, 2015)
Even that orodispersible tablets (ODTs) have been successfully used in therapy for more than 20 years, there is still no compendial method of their disintegration time evaluation other than the pharmacopoeial disintegration test conducted in 800–900 mL of distilled water. Therefore, several alternative tests more relevant to in vivo conditions were described by different researchers. The aim of this study was to compare these methods and correlate them with in vivo results. Six series of ODTs were prepared by direct compression. Their mechanical properties and disintegration times were measured with pharmacopoeial and alternative methods and compared with the in vivo results. The highest correlation with oral disintegration time was found in the case of own-construction apparatus with additional weight and the employment of the method proposed by Narazaki et al. The correlation coefficients were 0.9994 (p < 0.001), and 0.9907 (p < 0.001) respectively. The pharmacopoeial method correlated with the in vivo data much worse (r = 0.8925, p < 0.05). These results have shown that development of novel biorelevant methods of ODT’s disintegration time determination is eligible and scientifically justified.